A Simple Eco-friendly Titrimetric Analytical Method To Estimate Ketoprofane In The Bulk Drug Sample Using Mixed Hydrotrophy - DEEPIKA SINGH,; AMIT KUMAR SHARMA,; OMPRAKASH PANDEY,; MITHUN SINGH RAJPUT, (International Journal of Pharma and Bio Sciences, 2010)
The present investigation illustrates the application of mixed hydrotropy. There was a miraculous synergistic effect on enhancement in solubility of a practically water insoluble drug by mixing three hydrotropic agents. The enhancement in the solubility of ketoprofen in a mixed hydrotropoic solution containing 30% urea, 11.8% sodium citrate and 13.6% sodium acetate was more than 560 fold (as compared to the solubility in distilled water). This proved a synergistic enhancement in solubility of a practically water insoluble drug due to mixed hydrotropy. Mixed hydrotropic solution was employed to solubilize a practically water insoluble drug, ketoprofen, in bulk to carry out titrimetric analysis precluding the use of organic solvents. The bulk containing ketoprofen was analyzed successfully. Statistical data proved accuracy, reproducibility and the precision of the proposed method. The presence of hydrotropic agents (urea, sodium acetate and sodium citrate) did not interfere in the analysis.